Analisis Bahaya dan Risiko Banjir Berbasis Multikriteria di Kecamatan Sirimau Kota Ambon - Lasaiba, Mohammad Amin; Leuwol, Ferdinand S (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2024)
This study targets the threat and risk of flooding in Sirimau District, Ambon City, from a multi-criteria perspective using a Geographic Information System (GIS). Important flood hazard characteristics include land use, elevation, slope, distance from rivers, soil, and rainfall. Two risk factors, namely population density, land use, and flood hazard characteristics are used in flood risk analysis. Map aggregation procedure for flood risk and hazard analysis uses the Weighted Linear Combination (WLC) approach. The results of the flood hazard at the study site revealed that the flood hazard category was very high and high. Namely, 12.26% and the flood hazard category was very low and low, 87.84% and only. The results of the flood risk in the research location revealed that the flood risk with very high and high-risk categories was around 17.28%, and deficient and low flood risk categories (82.77%). This is because hilly and mountainous areas mostly dominate the Sirimau sub-district